Calculating the Gross Regional Product of the Kurdistan Region-Iraq - Abramzon, Shmuel (RAND Corporation, 2016)
This report presents estimates of the gross regional product (GRP) of the Kurdistan Region-Iraq in 2012 (excluding natural resources, because of lack of available data). It also describes efforts to set up a system for continuing data collection and analysis to support the annual calculation of the GRP, a critical indicator for successful policy planning.